Evaluation Cytotoxic and Anti-Cancer Effects of Salvia Officinal’s Leave Sex Tracts against Some of Cancer Cell Lines - Amal Rasheed Farhan (Journal of Global Pharma Technology, 2018)
The free radical scavenging actions were studied using DPP Has stable free radical compound in this paper. Consequences revealed that the increasing in extract concentration the more scavenging free radicals percent. The ranged concentrations (26.2 to 1000µg/ml) that were used, nevertheless the Ascorbic acid extract of S. officinal’s significantly displayed the highest antioxidant activity (86% at 1000µg/ml) among Methanol, Ethyl acetate and hexane extracts which were 84.5.1% , 56% and 54% respectively at 1000µg/ml. This work also aimed to study the cytotoxic and anticancer effects of Salvia officinal’s Leaves extract on some cell lines, The most significant reduction in viable count cell was 400 µ/ml which related to ascorbic acid extracts  appeared to cause the induction of cell lose  spatially in the cell lines A549, HepG2, MCF-7 respectively.Keywords: Salvia officinal’s, Cancer cell lines, DPPH, Cytotoxicity.